A population-based study of unintentional injury and premature death among non-imprisoned and imprisoned youth offenders - Siponen, R; Andersson, A; Oskarsson, S; Garcia-Argibay, M; Beckley, AL; Långström, N; Fazel, S; Chang, Z; Larsson, H; Evans, B; Tuvblad, C (Elsevier, 2022)
Background Youth offenders have a high risk of being injured or dying prematurely. However, few studies have considered the role of imprisonment and potential childhood risk factors for these high rates.